Media literacy, a vaccine against disinformation in the era of RICT - Marta-Lazo, Carmen (Anuario ThinkEPI, 2023)
In the era of relationship, information, and communication technologies (RICTs, or TRIC in Spanish), a great revolution has taken place in terms of the quantity and quality of information available. This overwhelming supply of content causes oversaturation, an overload of constant impacts created by millions of sources, which generates a large volume of information pollution. The vortex and speed of the way in which messages thus circulate result in unrestrained use and consumption and, at the same time, the processing of information through cognitive shortcuts that prevent us from analyzing and delving deeper into their meaning. Disinformation is a pandemic for which society is unprepared and needs to be addressed, as it is one of the greatest dangers for citizen destabilization, threatening public freedom and democracy. Media literacy is the formula to provide defense mechanisms against this important social disease. Knowing how to filter information and compare sources is necessary to awaken criticism. At the same time, it is necessary for citizens, as message-creating agents, to be aware of the transcendence of the content they broadcast and to know how to measure the possible impact of what they produce, taking on authorship but with criteria and responsibility.
Keywords: Media literacy; Disinformation; Emirec; Relational factor; TRIC; RICT; Digital competences